Human resources and Islamic microﬁnance sustainability: an empirical study of Baitul Maal wat Tamwil in Indonesia - Dawami, Qosdan; Abdul Razak, Dzuljastri; Hamdan, Hamdino (Riphah Centre of Islamic Business (RCIB), 2021)
The main purpose of this study is to determine empirically the relationship between human resource adequacy and the sustainability of BMT in Indonesia. This study used triangulation design as its research method. The total number of 285 questionnaires were distributed manually to BMT staﬀs and analyzed using SPSS. In addition, this study also conducted semi-structured interviews with some managers of BMT.. The results indicated that human resource resource adequacy has a significant impact on the sustainability of BMT an the relationship is positive. .